PENINGKATAN KETERAMPILAN MENULIS HURUF JAWA DENGAN MEDIA BALAPAN â€œBEDHEKAN WANGSALAN PRAPATANâ€ PADA SISWA KELAS VII F SMP NEGERI 4 KOTA MAGELANG - Yustina Tri Retno Sri Rachmiwati (TRANSFORMATIKA, 2015)
Wangsalan has the potential interest of students in learning the Java language since it has elements of games and entertainment. Bedhekan items in wangsalan can be arranged in the form of crossword puzzles or in Javanese language better known with the term prapatan. The composition of the bedhekan wangsalan in the later abbreviated BALAPAN (Bedhekan Wangsalan Prapatan). The use of this medium can be used as an alternative to the Java language learning techniques, including writing letters to fill in the fields using the Java letters of Java. The Media is expected to overcome boredom and a sense of saturation of students in the learning process. Learning to write Java letter with the media BALAPAN can improve the ability of students in writing letters of Java. This is evident from the results of the study showed that the average value of Pracycle, The Cycle I, and Cycle II has increased. The average value of Pracycle of the I and the Cycle of 59,29 74,46 or increased by 25.6%. The value of the Cycle I and Cycle II 74,46 $ 86.25% 15,83 or increased. Overall improvement of writing skills of Java Pracycle letter to the Cycle II experienced an increase of 45,28%. Behavior change in the learning activities of students also experience a change to the better. A learning recreatif media is able to encourage the interest and motivation of students at the time of learning. Students are more motivated in my experience, learn, and discover knowledge, build understanding, communicating the results of his thinking, and more reflective thinking.Â Keywords: Bedhekan Wangsalan Prapatan, wangsalan, media, creatif learning.